1981
DOI: 10.3758/bf03333718
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for accented and unaccented voices

Abstract: Laboratory research has established that face recognition memory performance for ownrace faces is better than for other-race faces. Three studies are reported exploring the possibility that the other-race effect will generalize to voice recognition memory. Recognition memory performance for non-native American speakers speaking both English and their native languages was compared with memory for native American speakers. With relatively long speech samples, accented voices were no more difficult to recognize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…The study by Goldstein et al (1981) supports the hypothesis that accented voices are more difficult to recognize than unaccented voices, but the evidence for a foreign-language effect in SID does not seem to be particularly strong. However, the conclusion that 'voice recognition is just as good (or as poor) for foreign voices as it is for native voices' seems premature to us since their second experiment revealed a significant effect for the Chinese speakers.…”
Section: Speaker Identification Without Linguistic Informationsupporting
confidence: 64%
See 3 more Smart Citations
“…The study by Goldstein et al (1981) supports the hypothesis that accented voices are more difficult to recognize than unaccented voices, but the evidence for a foreign-language effect in SID does not seem to be particularly strong. However, the conclusion that 'voice recognition is just as good (or as poor) for foreign voices as it is for native voices' seems premature to us since their second experiment revealed a significant effect for the Chinese speakers.…”
Section: Speaker Identification Without Linguistic Informationsupporting
confidence: 64%
“…In their second experiment, however, Goldstein et al (1981) reduced the length of the speech material to which listeners were exposed before they performed the recognition task. The reduction of the speech stimulus to a single word had the effect of reducing the overall percentage of correctly recognized voices considerably, especially for the Chinese target voices.…”
Section: -1771mentioning
confidence: 99%
See 2 more Smart Citations
“…I In such cases, a question arises concerning the degree to which the nativelanguage background of the witness influences his or her ability to recognize a speaker audirorily, Very little empirical data are available on this topic to date. Goldstein et al (1981) reported an experiment in which subjects (native American English listeners) were asked to identify voices with and © Routledge 1996 ForensicLinguistics3 (I) 1996: 176--185 1350--1771 without a foreign accent. Results showed that they performed equally well in recognizing accented and non-accented voices.…”
Section: Introductionmentioning
confidence: 99%